Bugental And The Art Of Being (Existential Analysis: Journal of the Society for Existential Analysis, 2018)
This paper analyses Jim Bugental's scholar-practitioner work as means of guiding clients to reinvigorate their existential identities. It explores literature spanning Bugental's career, arguing that existential-humanistic psychotherapy, a term he coined, is a powerful means to aid clients in manoeuvring the course of their lives because of its focus on universal existential concerns.
Keywords: Bugental; existential-humanistic psychotherapy; being